Evaluation in the Crowd : Crowdsourcing and Human-Centered Experiments : Dagstuhl Seminar 15481, Dagstuhl Castle, Germany, November 22-27, 2015 : revised contributions /: Dagstuhl Seminar 15481, Dagstuhl Castle, Germany, November 22-27, 2015 : revised contributions. (2017) - Unknown
No abstract available